Taipei Fine Arts Museum Collection Catalogue 2004. (Taipei : Taipei Fine Arts Museum Taipei, 2004)
Chen Chi-Kwan ; Cheng Shan-Hsi ; Fong Chung-Ray ; Yuan Chin-Ta ; Hsu Yu-Jen ; Li Mao-Cheng ; Huang Chih-Yang ; Ting Chi-Pan ; Lin Ko-Kung ; Wu Tong-Tsai ; Lee Yeong-Two ; Tseng Pei-Yao ; Jan Syue-Fu ; Yang Cheng-Yuan ; Abugy (Chan Hsien-Kun) ; Lai Chiu-Chen ; Liao Yu-An ; Chiou Jyian-Ren ; Chou Ming-Yi ; Massey, Charles ; Chang-Li Fu ; Hung Tung ; Lee, Daniel ; Kuo Ying-Sheng ; Lu Ming-Te ; Wu Tien-chang ; Tseng Yu-Chin ; Li Guo-Cheng ; Yan Shui-Long ; Yang Chih-Hsin ; Lee Ti-Chin ; Liu An-Ming ; Gojo Kinju ; Hsieh Chen-Lung ; Wong Ting-Hua ; Chen, Attow ; Chuang Ling ; Chang Chao-Tang ; Huang Yung-Sung ; Yau Meng-Jia ; Kuo Hsien-Tang ; Kuan Hsiao-Jung ; Lin Bor-Liang ; Hsieh San-Tai ; Yuan Goang-ming ; Sheu Jer-Yu
Engels
Taiwanees
boek